1990
DOI: 10.1097/00005072-199003000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Selective Disconnection of Specific Visual Association Pathways in Cases of Alzheimer's Disease Presenting with Balint's Syndrome

Abstract: During a recent clinical and neuropathological evaluation of a large autopsy population of brains our attention was drawn to a subset of patients with Alzheimer's disease (AD) presenting with a major impairment of visuospatial skills referred to as Balint's syndrome. In this subset a shift in the distribution of certain pathological profiles had occurred in that the visual areas of the occipital and posterior parietal regions had an increased number of lesions, whereas the prefrontal cortex had fewer lesions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
83
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 218 publications
(95 citation statements)
references
References 0 publications
9
83
0
3
Order By: Relevance
“…Saito (1993) has shown that human performance in direction discrimination as a function of coherence is closely matched by directional response functions of type D cells in the dorsal part of area MST. Finally, some recent studies with Alzheimer patients (e.g., Hof, Bouras, Constantinidis, & Morrison, 1989;Trick & Silverman, 1991) suggest that the decreased motion sensitivity (i.e., the strongly elevated coherence thresholds) of these patients is due to disruption of the occipitoparietal pathway. Taken together, these results indicate that areas MT and MST playa crucial role in the spatiotemporal integration of motion signals.…”
Section: Coherence In Random Dot Displays: a Tool For Investigating Mmentioning
confidence: 95%
“…Saito (1993) has shown that human performance in direction discrimination as a function of coherence is closely matched by directional response functions of type D cells in the dorsal part of area MST. Finally, some recent studies with Alzheimer patients (e.g., Hof, Bouras, Constantinidis, & Morrison, 1989;Trick & Silverman, 1991) suggest that the decreased motion sensitivity (i.e., the strongly elevated coherence thresholds) of these patients is due to disruption of the occipitoparietal pathway. Taken together, these results indicate that areas MT and MST playa crucial role in the spatiotemporal integration of motion signals.…”
Section: Coherence In Random Dot Displays: a Tool For Investigating Mmentioning
confidence: 95%
“…In particular, a careful analysis of such cases revealed that in this population, the hippocampal formation systematically displayed a moderate to severe involvement, whereas the neocortical areas were unaffected or showed very low densities of NFTs and SPs Arriagada et al, 1992a ;Berg et al, 1993;Bouras et al, 1993). This difference in regional lesion distribution distinguishes these elderly nondemented cases from the Alzheimer's disease population, in which neocortical areas are devastated (Pearson et al, 1985;Lewis et al, 1987;Hof et al, 1990aHof et al, ,b, 1992Bouras et al, 1992). Most of the recent clinicoanatomic analyses of brain aging have been based on relatively small patient samples consisting of selected cases (Crystal et al, 1988;Katzman et al, 1988;Hubbard et al, 1990;Morris et al, 1991;Price et al, 1991;Arriagada et al, 1992a,b;.…”
mentioning
confidence: 92%
“…In fact, Hyman and colleagues have demonstrated that the presence of NFTs in layer II of the entorhinal cortex was correlated by the presence of pathologic profiles in the termination zone of the perforant pathway in the outer portion of the molecular layer of the dentate gyrus, implying that this cortical pathway is severely affected in Alzheimer's disease cases (Hyman et al, 1988). In addition, the distribution of NFTs and SPs in the neocortex and in the hippocampal formation suggests that SP formation may involve the terminal arborization of NFT-bearing neurons (Pearson et al, 1985;Rogers and Morrison, 1985;Lewis et al, 1987;Hof and Morrison, 1990;Hof et al, 1990a;Senut et al, 1991;De Lacoste and White, 1993).…”
mentioning
confidence: 99%
“…This suggests that selected cortical pathways linking the primary visual regions to the posterior parietal and cingulate visual association cortex may be involved in the early stage of the AD. Hof et al (37) found an increased number of lesions in the visual areas of the occipital and posterior parietal regions in AD patients presenting with Balint's syndrome. Similarly, using positron emission tomography (PET) in patients with the visual variant of AD, Pietrini et al (38) and Nestor et al (39) found selective hypometabolism in the occipitoparietal regions.…”
Section: Pathology In Humansmentioning
confidence: 99%